Eating disorder symptoms among children and adolescents in Germany before and after the onset of the COVID-19 pandemic - Napp, Ann-Kathrin; Kaman, Anne; Erhart, Michael; Westenhöfer, Joachim; Ravens-Sieberer, Ulrike (Frontiers in Psychiatry, 2023)
Background Disordered eating is highly prevalent among children and adolescents. Since the outbreak of the COVID-19 pandemic, hospitalizations due to eating disorders have peaked and overweight has risen. The aim of this study was to determine differences in the prevalence of eating disorder symptoms among children and adolescents in Germany before and after the onset of the COVID-19 pandemic and to identify associated factors. Materials and methods Eating disorder symptoms and associated factors were examined in a sample of n = 1,001 participants of the nationwide population-based COPSY study in autumn 2021. Standardized and validated instruments were used to survey 11–17-year-olds along with a respective parent. To identify differences in prevalence rates, logistic regression was used to compare results with data from n = 997 participants of the prepandemic BELLA study. Multiple logistic regression analyses were performed to examine associations with relevant factors in the pandemic COPSY sample. Results Eating disorder symptoms were reported by 17.18% of females and 15.08% of males in the COPSY study. Prevalence rates were lower overall in the COPSY sample compared to before the pandemic. Male gender, anxiety, and depressive symptoms were associated with increased odds for eating disorder symptoms in the pandemic. Conclusion The pandemic underscores the importance of further research, but also prevention and intervention programs that address disordered eating in children and adolescents, with a focus on age - and gender-specific differences and developments. In addition, screening instruments for eating disorder symptoms in youths need to be adapted and validated.